PENGELOLAAN DAN PENGEMBANGAN KEGIATAN EKSTRAKURIKULER OLAHRAGA DI SMA/MAN/SEDERAJAT SE-KABUPATEN SLEMAN - Fathan Nurcahyo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
This study aims to determine the management system and the development of sports in high school extracurricularactivities/ MAN/ equivalent in Sleman, Yogyakarta in 2012. This research is a descriptive qualitative-quantitative.The method used in this study is a survey method to test the technique. Subjects in this study were all high schoolorchestra teacher of sports education/ MAN/ equivalent in Sleman district, Yogyakarta in 2012, taken by incidentalsampling, i.e. all orchestra teacher of sports education who attended the event MGMPs SMA/ MAN who totaled 13orchestra teacher of sports education. The instrument used for data collection in this study using an open questionnaireinstrument. Data analysis techniques in this study using descriptive statistical analysis with qualitative - quantitativepercentages. The results showed that of the 13 teachers in 13 high schools / MAN / equivalent in Sleman, Yogyakartain detail there are 12 schools have implemented the management and development of sport extracurricular activitieswith good and only 1 school who have not: (1) The function of organizing, from 13 schools there are 7 schools thathave a stewardship organization chart and the 6 school teachers feel no idea. (2) Planning functions are arranged intwo groups: long-term plans and short-term. (3) The function of most of the schools decision made are determinedthrough consensus agreement with the involvement of managers, coaches, students, principals, and sometimesinvolve parents or the school committee. (4) The function of supervision/ leadership (decision-making related functions)mostly use the democratic leadership style (negotiate). (5) The function of control and control systems mostly usebooks and monitoring presence on the ground. (6) The function improvement, evaluation and assessment systemsmostly use the practice test that is conducted every semester. (7) Planning staff and personnel functions, related to theway the selection or hiring coaches conducted collaboratively between an open and a closed selection has the samepower (balanced). And (8) financial budgeting function, most of the operational funding comes from parent parents.